2015
DOI: 10.3389/fncel.2015.00346
|View full text |Cite
|
Sign up to set email alerts
|

Surgery plus anesthesia induces loss of attention in mice

Abstract: There is a need to develop animal models to study postoperative delirium. Inattention is one of the symptoms of delirium. Increases in the levels of α-synuclein and S100β have been reported to be associated with delirium. Therefore, we set out to determine the effects of surgery plus general anesthesia on the behavioral changes (including loss of attention) in mice and on the levels of α-synuclein and S100β in the brain tissues of these mice. C57BL/6J mice (2- to 8-months-old) had a simple laparotomy plus isof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…Anesthesia and surgery (anesthesia/surgery) in rodents have been shown to induce cognitive impairment [( 1 10 , 33 ), reviewed in Ref. ( 11 )].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anesthesia and surgery (anesthesia/surgery) in rodents have been shown to induce cognitive impairment [( 1 10 , 33 ), reviewed in Ref. ( 11 )].…”
Section: Discussionmentioning
confidence: 99%
“…The 18-month-old mice are only available through National Institute of Aging, thus cannot be purchased from same company that provides the 9-month-old mice. Mice in the anesthesia/surgery group had a simple laparotomy under isoflurane anesthesia using the methods described in our previous studies ( 10 , 33 ). Specifically, we anesthetized each of the mice using 1.4% isoflurane in 100% oxygen in a transparent acrylic chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, surgery/anesthesia exposure could alter the normal dynamics of both neuroinflammation and oxidative stress simultaneously, leading to an unhealthy state for the brain and cognitive dysfunction. Ren et.al found that surgery plus isoflurane could induce postoperative delirium and associated biochemical/cellular changes in mice . Surgery/anesthesia exposure model is closer to clinic practice.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et.al found that surgery plus isoflurane could induce postoperative delirium and associated biochemical/cellular changes in mice. 10 Surgery/anesthesia exposure model is closer to clinic practice. However, the underlying mechanisms of neuroinflammation and oxidative stress on postoperative cognitive impairment remain still unclear.…”
mentioning
confidence: 99%